Discovery and Characterisation of Highly Cooperative FAK‐Degrading PROTACs. (17th September 2021) - Law, Robert P.; Nunes, Joao; Chung, Chun‐wa; Bantscheff, Marcus; Buda, Karol; Dai, Han; Evans, John P.; Flinders, Adam; Klimaszewska, Diana; Lewis, Antonia J.; Muelbaier, Marcel; Scott‐Stevens, Paul; et al.
Abstract: Focal adhesion kinase (FAK) is a key mediator of tumour progression and metastasis. To date, clinical trials of FAK inhibitors have reported disappointing efficacy for oncology indications. We report the design and characterisation of GSK215, a potent, selective, FAK‐degrading Proteolysis Targeting Chimera (PROTAC) based on a binder for the VHL E3 ligase and the known FAK inhibitor VS‐4718. X‐ray crystallography revealed the molecular basis of the highly cooperative FAK‐GSK215‐VHL ternary complex, and GSK215 showed differentiated in‐vitro pharmacology compared to VS‐4718. In mice, a single dose of GSK215 induced rapid and prolonged FAK degradation, giving a long‐lasting effect on FAK levels (≈96 h) and a marked PK/PD disconnect. This tool PROTAC molecule is expected to be useful for the study of FAK‐degradation biology in vivo, and our results indicate that FAK degradation may be a differentiated clinical strategy versus FAK inhibition for the treatment of cancer. Abstract : A PROTAC with an unusually short linker potently degrades focal adhesion kinase (FAK). SPR and X‐ray crystallography revealed a highly cooperative FAK‐PROTAC‐VCB ternary complex, and FAK degradation showed enhanced effects on 3D cell growth compared to FAK inhibitors. In mice, GSK215 induced rapid and sustained degradation of FAK with a profound PK/PD disconnect.